2012
DOI: 10.3109/15622975.2012.665480
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in anxiety and depressive symptoms in patients with primary hyperaldosteronism: A cross-sectional study

Abstract: This study supports the RAAS to be involved in the pathogenesis of depression as patients with PA seem to be more depressive and anxious compared to the normal population. Gender differences in the regulation of the RAAS seem to be apparent, as females were more affected by the dysregulation than males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 69 publications
3
49
0
1
Order By: Relevance
“…Häfner et al [31,32] demonstrated specific factors for an increased level of aldosterone in depression, in particular a co-occurrence with arterial hypertension and with social isolation. Further support of a causal role of aldosterone comes from observations that patients with primary hyperaldosteronism frequently show symptoms of depression, anxiety and somatization and a reduced quality of life [33,34,35]. A direct causal involvement of aldosterone is also suggested by animal data: subchronic administration of aldosterone with a minipump led to depression- and anxiety-like behavior in rats [24].…”
Section: Mr and The Stress Hormone Systemmentioning
confidence: 92%
“…Häfner et al [31,32] demonstrated specific factors for an increased level of aldosterone in depression, in particular a co-occurrence with arterial hypertension and with social isolation. Further support of a causal role of aldosterone comes from observations that patients with primary hyperaldosteronism frequently show symptoms of depression, anxiety and somatization and a reduced quality of life [33,34,35]. A direct causal involvement of aldosterone is also suggested by animal data: subchronic administration of aldosterone with a minipump led to depression- and anxiety-like behavior in rats [24].…”
Section: Mr and The Stress Hormone Systemmentioning
confidence: 92%
“…PA has been associated with depression (28,262,303), anxiety (21,270,473,474), and even episodic rage (which resolved after unilateral adrenalectomy for APA) (236 …”
Section: Adverse Psychological Effects and Impaired Quality Of Lifementioning
confidence: 99%
“…Nocturia is a common symptom even among patients with normal plasma potassium levels, possibly because of the rise in ANP levels that has been observed among patients with PA, or because an increase in potassium release from renal tubular cells (serving as an attempt to maintain normokalemia) may have led to an intracellular potassium deficit. Patients with PA also frequently describe feelings of lethargy, impaired mental concentration, and mood disturbances (9,21,28,270,473,474,509). During pregnancy, hypertension and symptoms may improve (49,210,424).…”
Section: Symptoms and Signs Of Pamentioning
confidence: 99%
“…[43][44][45][46][47][48][49][50] There is also mounting evidence for development of type 2 diabetes, insulin resistance and the metabolic syndrome, 51-54 obstructive sleep apnea, 55 renal disease, 56-58 psychiatric disease, 59 and bone loss 60 in patients with untreated aldosterone excess.…”
Section: Pathophysiology and Geneticsmentioning
confidence: 99%